Building Digital Literacy As An Editorial Problem (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the modernity, creativity and positive effect of digital literacy skills formation in the educational process, as well as the fact that digital literacy allows students to learn at a convenient time and place, and the problems of modern pedagogy